Behaviour of acid secretion, gastrin release, serum pepsinogen I, and gastric emptying of liquids over six months from eradication of helicobacter pylori in duodenal ulcer patients. A controlled study. Issue 2 (August 1995) - Parente, F; Maconi, G; Sangaletti, O; Minguzzi, M; Vago, L; Bianchi Porro, G
Abstract : The behaviour of basal and stimulated acid secretion, gastrin release, serum pepsinogen I, and gastric emptying of liquids was studied in 19 consecutive patients with Helicobacter pylori positive duodenal ulcer, over a follow up period of six months. Eleven patients were studied before and at three and six months after eradication with lansoprazole plus amoxicillin and tinidazole (case group), whereas the remainder, with persistent H pylori infection, were studied before and after three and six months from ulcer healing, thus constituting the control group. In the case group, three months after eradication, fasting serum pepsinogen I fell from (mean (SEM)) 91.9 (6.9) (pretreatment) to 72.2 (5.1) ng/l and the integrated gastrin response to a meal reduced from 11, 470 (1174) (pretreatment) to 8130 (608) pg/ml/h (p < 0.05). Fasting serum gastrin concentrations and maximal acid output reduced significantly only six months after eradication. In contrast, no significant change of any of these measurements was seen in the control group either at three or six months from healing compared with the pretreatment values. Gastric emptying of liquids did not change over the entire period of follow up in both study groups. In conclusion, eradication of H pylori in duodenal ulcer patients is accompanied by a rapid fall in serum pepsinogen I and plasma gastrin concentrations, whereas a slight but significant reduction of maximal acid secretion takes place later on. In contrast, gastric emptying of liquids does not seem to be influenced by H pylori status.